Anemia of prematurity: a narrative review - Sónia Andrade Santos; Gustavo Rocha; Henrique Soares (Portuguese Journal of Pediatrics)
Anemia of prematurity is a condition that is prevalent in neonatal intensive care units, especially among extremely low birth weight infants. Despite extensive practice and research, several preventive and therapeutic strategies remain controversial, giving rise to significant differences among centers. Preventive strategies include delayed cord clamping, umbilical cord milking, autologous and allogeneic cord blood transfusion, and reducing iatrogenic blood loss through innovative methods like microsample devices. The effectiveness of erythropoiesis-stimulating agents in reducing transfusions remains limited. Red blood cell transfusions, while beneficial, carry risks. Defining transfusion thresholds based on hemoglobin levels remains a challenge, with practices varying globally. Recent trials advocate for a restrictive transfusion approach, reducing the number of transfusions with no significant adverse effects. Near Infrared Spectroscopy evaluates tissue oxygenation, potentially aiding transfusion decisions based on individualized physiological markers of anemia. This review provides a summary of the latest literature on anemia of prematurity, emphasizing aspects related to pathophysiology, preventive measures, and therapeutic interventions to assist clinicians in managing this condition.